PENGUATAN PENGGUNAAN MEDIA PEMBELAJARAN DALAM MENGHAFAL KOSA KATA BAHASA ARAB DI PTUQI CIBUNGBULANG BOGOR - Abrar, Muh. (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2025)
This empowerment aims to provide assistance to several children at Pondok Tahfidz Ummul Quro Al-Islami Bogor in memorizing the Arabic vocabolary about limbs through self-creativity with learning media that can be used in every learning, especially at the level of basic education and generally for various levels of education. Based on the results of the research that has been carried out, it can be concluded that the assistance of learning media skills in memorizing the Arabic vocabolary shows students' interest in memorizing the Arabic vocabolary by applying learning media skills to be more creative and fun. This learning media skill can be used as an alternative for students to develop their own creativity, so that it becomes a shortcut to make it easier to understand the material being taught and avoid boredom. This service explained about the assistance of learning media skills in memorizing the Arabic vocabolary for students at PTUQI Cibungbulang Bogor about how the process of making Arabic learning media skills aimed at making it easier to memorize vocabolary about limbs. However, this media is not limited to the memorization method only and can be continued to learn other methods of discussion. In addition, this research only includes the creation of learning media skills, even though there are still many other skills that can be taught to students to form their own creativity.